The Relationship Between Knowledge About The Immunity System And Behaviours Of Maintaining Immunity In Nurses During The Covid-19 Pandemic - Hamdana; Amirullah; Supardy; Nursamsi (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
The main disease Coronavirus Disease 2019 (Covid-19). Covid-19 is classified as a new virus for the human body's immune system so it does not have a natural immune system can fight the virus. Seeing the ease with which Covid-19 is transmitted and the high and increasing cases is of particular concern to health workers who are at the forefront of treating patients, especially nurses. Nurses as one of the health workers who provide services to patients in the hospital for 24 hours are at high risk of infection. Based on data from the Health Influence Index for Health Workers as of 21 July 2020,ratio of deaths medical personnel and health workers compared to total confirmed Covid-19 deaths in Indonesia has reached 2.4% and one of highest compared to other countries. Emergency and Special Isolation Rooms, like it or not, have an obligation to be ready to be at the forefront of struggling with a virus that is very deadly and can infect them, not to mention the condition of fatigue and nutrition that they even have enough of while busy caring for patients. their immunity decreases so that it is easier for the virus to enter to attack the immune system in these nurses. Efforts to prevent and transmit Covid-19 to nurses, one of the health workers, must be carried out and tightened to minimize the continued rise of Covid-19 cases in health workers. The Indonesian Ministry of Health has issued a Guide to Balanced Nutrition During the COVID-19 Pandemic.